Acute effects of training load on contractile properties during a competitive microcycle in elite soccer players - Rey, Ezequiel; Corredoira, Francisco; Costa, Pablo B.; Pérez-Ferreirós, Alexandra; Fernández-Villarino, María (Biology of Sport, 2020)
The aim of this study was to examine changes in muscle contractile properties across a microcycle of training in professional soccer players during the in-season period. Nineteen professional soccer players were assessed with tensiomyography (TMG) on the biceps femoris and rectus femoris before and after 5 training sessions of an in-season microcycle. Training load was quantified during each training session. Significant differences were observed in training load variables across different training sessions, with the last training session prior to match day showing the lowest values for all training load variables. Significant pre- to postsession increases were observed in muscle stiffness of the rectus femoris and biceps femoris during the first four training sessions (effect size range, 0.5 to 0.9). However, no significant differences were observed in muscle contraction time and contraction velocity from pre- to post-session. In addition, repeated measures correlation analysis revealed significant relationships between absolute change in muscle stiffness of the rectus femoris and training duration, high-speed distance covered during training, and training average distance. The current study shows that players are physically taxed on their muscular stiffness by the training load. Post-session muscular stiffness assessment should be recommended to determine neuromuscular status and readiness in professional soccer players during the competitive season.